2014
DOI: 10.1037/a0038205
|View full text |Cite
|
Sign up to set email alerts
|

Head Start’s impact is contingent on alternative type of care in comparison group.

Abstract: Using data (n = 3,790 with 2,119 in the 3-year-old cohort and 1,671 in the 4-year-old cohort) from 353 Head Start centers in the Head Start Impact Study, the only large-scale randomized experiment in Head Start history, this paper examined the impact of Head Start on children’s cognitive and parent-reported social-behavioral outcomes through first grade contingent on the child care arrangements used by children who were randomly assigned to the control group (i.e., parental care, relative/non-relative care, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 55 publications
1
48
1
Order By: Relevance
“…Several recent studies have examined how the estimated end-of-treatment impacts of Head Start vary depending on the comparison group using the HSIS, and find indeed that the main end of treatment effect for Head Start is strongest when compared with children in the control group who attended home-based care, with few to no differences compared with center-based care (Feller, Grindal, Miratrix, & Page, 2016; Kline & Walters, 2016; Walters, 2015; Zhai, Brooks-Gunn, & Waldfogel, 2014). Bloom and Weiland (2015) find substantial heterogeneity in Head Start treatment impacts by program site, with centers ranging from much more to much less effective than their local alternatives, including parent care.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined how the estimated end-of-treatment impacts of Head Start vary depending on the comparison group using the HSIS, and find indeed that the main end of treatment effect for Head Start is strongest when compared with children in the control group who attended home-based care, with few to no differences compared with center-based care (Feller, Grindal, Miratrix, & Page, 2016; Kline & Walters, 2016; Walters, 2015; Zhai, Brooks-Gunn, & Waldfogel, 2014). Bloom and Weiland (2015) find substantial heterogeneity in Head Start treatment impacts by program site, with centers ranging from much more to much less effective than their local alternatives, including parent care.…”
Section: Discussionmentioning
confidence: 99%
“…Using a matching approach, Zhai et al (2014) find significant effects of Head Start compared to parent care and relative/nonrelative care but find no meaningful differences in outcomes between Head Start and other center-based care. Using variation across sites, Walters (2015) finds that impacts are smaller for Head Start centers that draw more children from other center-based programs rather than from home-based care.…”
Section: Heterogeneity By Alternative Care Typementioning
confidence: 99%
“…5 This approach improves on simpler versions of this model fit by Walters (2015) and Zhai et al (2014). Walters (2015) effectively estimates the share of Center-based Compliers and Home-based Compliers for each Head Start center, doing so via two separate logistic regressions, rather than via multinomial logistic regression.…”
Section: Lemma 2 (Distribution Of Covariates By Principal Stratum) Umentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Zhai et al [14] using data from the National Head Start Impact Study found children in the program had greater cognitive and behavioral development compared with their peers who were not in the program. Another study using data from the Early Childhood Longitudinal Study-Birth Cohort comparing children enrolled in Head Start and those in parental or nonparental childcare found children in the program had greater school readiness, as indicated by higher early reading and math scores [15].…”
Section: Lasting Results Of Supportive Programsmentioning
confidence: 99%